Program Corporate Social Responsibility PT. Petrokimia Gresik - Anandya Zalva Yunnafisah; Bowo Santoso (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The role of Corporate Social Responsibility (CSR) in improving community welfare is the focus of this research, which is influenced by the relationship between companies and communities that develop along with the development and civilization of society. This study aims to determine the role of Corporate Social Responsibility for community welfare in its implementation. The activity stages were designed for 1 day, preceded by coordination activities. The CSR program in the economic field for the community around PT Petrokimia Gresik is by distributing Ramadan groceries in 8 villages around PT Petrokimia Gresik, namely Kroman Village, Tlogopojok, Roomo, Lumpur, Sukorame, Karangpoh, Karangturi, and Ngipik.